Aggressive posterior retinopathy of prematurity - Tateshi, Bekim; Isjanovski, Igor; Dimovska Jordanova, Vesna; Oros Ana (SHMSHM / AAMD, 2014)
AbstrAct Medicus 2014, Vol. 19 (2): 364 -367 case report Retinopathy of prematurity (ROP) is a disease that occurs in premature infants and affects the blood vessels of the developing retina. Aggressive Posterior Retinopathy of Prematurity-AP ROP, sometimes referred to as Rush desease, is a rapidly progressive form of ROP. Less experienced examiners may easily miss the diagnosis in its early stages, resulting in a significant delay in referral for treatment. Clinicians should be keenly aware of this aggressive variant of ROP. In this study we present a female infant borne at 28th weeks gestation with birth weight of 950 gr. First dilated funduscopic examination was done on 32nd gestational age and revealed immature retina on both eyes with no clear demarcation line. One week later we repeat examination, on funduscopic examination there was plus disease accompanied by vascularization ending in Zone I, flat stage 3 disease on both eyes. Retinal laser photocoagulation was performed at this time. The use of diode laser therapy in extremely preterm infants with ROP appears not only to halt disease progression but also leads to good visual outcomes for most of these infants.
Агресивна постериорна прематурна ретинопатија
Keywords: Aggressive Posterior ROP; Screening for ROP; Retinal laser photocoagulation; Anti-VEGF agents